Why people stay: Decision-making in situations of forced displacement and options for humanitarian aid and development cooperation - Nadine Biehler (Stiftung Wissenschaft und Politik (SWP), 2023)
The proportion of affected populations who flee violent conflict is much smaller than is widely assumed. Many decide to remain in the conflict zones. They are often referred to as stayees. Three groups can be identified. Some people stay voluntarily. Others do so involuntarily, for example because they lack the resources to flee or because violent actors restrict their freedom of movement. Another group acquiesce to their immobility. Little is known about stayees, their needs and the reasons for their immobility. But several factors relevant to their decision-making can be identified. These include type of conflict, type of violence and personal situation. Whether they remain voluntarily or involuntarily, stayees employ survival strategies including collaboration, neutrality, protest and resistance. Knowledge about stayees and their survival strategies is important for humanitarian aid and development actors. Only if they are well informed can they align their activities with actual needs and provide meaningful support to people living in and with violent conflicts. It is therefore essential to consider the entire spectrum of (im)mobility and to understand this expanded perspective as a positive - without neglecting the forcibly displaced. The agency of civilians in violent conflicts needs to be recognised and they must be protected from abuse and exploitation by aid workers (do-no-harm principle). Finally, stayees must be systematically included in all post-conflict initiatives supporting voluntary return and reintegration.
Keywords: 320; displacement; internally displaced persons (IDPs); trapped populations; migration; asylum; stayees; humanitarian aid; development cooperation; violent conflicts; do-no-harm principle; return; reintegration; Germany; EU